Antimutagenic Activity of Ethanol Extract of Rhaphidophora pinnata (L.f) Schott Leaves on Mice - Masfria; Sumaiyah; Aminah Dalimunthe (MDPI AG, 2017)
Rhaphidophora pinnata is suggested to prevent or treat cancer of genetic mutations. In this study, antimutagenic activity of an ethanol extract of Rhaphidophora pinnata leaves was evaluated by using a bone marrow micronucleus assay on mice. Male mice (20-30 g) were treated for sevendays with an ethanol extract of Rhaphidophora pinnata leaves at a dose of 500, 750 and 1000 mg/kg/day/orally, prior to exposure to cyclophosphamide (i.p. 30 mg/kg), 24 h after the end of the treatment. Antimutagenic activity was determined by the decrease of micronuclei (MN). The results showed that a single administration of all variant doses of the extract had significantly decreased the micronucleus formation in bone marrow cell of mice as compared to the cyclophosphamide group. The ethanol extract of Rhaphidophora pinnata leaves had antimutagenic activity against cyclophosphamide-induced gene mutation.